BUILDING A COMMUNITY BASED ECOTOURISM WISATA DESA WAY KAMBAS IN BRAJA HARJOSARI: AN INDIRECT TOOL FOR WILDLIFE MITIGATION CONFLICT IN WAY KAMBAS NATIONAL PARK - Rustiati, Elly L. (Sakai Sambayan Jurnal Pengabdian kepada Masyarakat, 2017)
Abstract Way Kambas National Park is facing human-wildlife conflict due to most of its borderline with settlement areas. Braja Harjosari, one of 37 villages next to the national park, has agricultural damage and economy lost due to wildlife conflict especially sumatran elephant. Braja Harjosari has great landscapes including river, swamp and traditional agriculture; diverse culture and unique social daily life. Indirect approach for wildlife conflict mitigation has been done by exploration and empowerment of its natural potential resources for community based ecotourism program, called Wisata Desa Way Kambas. With the close accompaniment, the ecotourism program gives great alternative income for the local people in Braja Harjosari. This alternative creative economy may serve human-elephant conflict mitigation, and may play an important role for gradually changing local people negative perception on sumatran elephant. Keywords: Conflict mitigation, sumatran elephant, Braja Harjosari, Wisata Desa Way Kambas, ecotourism